2013
DOI: 10.1080/08870446.2013.800517
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported health and cortisol awakening response in parents of people with asperger syndrome: The role of trait anger and anxiety, coping and burden

Abstract: Caring for offspring with autism spectrum disorders entails high levels of stress for a long period of time and is associated with several types of health complaints. Few studies have focused on specific effects of particular disorders in the spectrum. This study was carried out with the aim of evaluating the global health of parents of people with Asperger syndrome (N = 53) compared to those of typically developing children (N = 54) through self-reported measures (medication consumption and somatic symptoms) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 52 publications
4
37
0
2
Order By: Relevance
“…These results replicate previous findings showing a high rate of anxiety/depression in parents of a child with GTS (Lee et al, 2007). It has been widely demonstrated that being parents of a child with a chronic disorder had a negative impact on the physical and mental health of parents in charge of his education (Lovell, Moss, & Wetherell, 2012;Ruiz-Robledillo & Moya-Albiol, 2013, Ruiz-Robledillo, González-Bono, & Moya-Albiol, 2014). This has been mostly shown in developmental disorders, particularly in ASD, as problem behaviors were identified to be a primary predictor of parental stress (Estes et al, 2013;Zaidman-Zait et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results replicate previous findings showing a high rate of anxiety/depression in parents of a child with GTS (Lee et al, 2007). It has been widely demonstrated that being parents of a child with a chronic disorder had a negative impact on the physical and mental health of parents in charge of his education (Lovell, Moss, & Wetherell, 2012;Ruiz-Robledillo & Moya-Albiol, 2013, Ruiz-Robledillo, González-Bono, & Moya-Albiol, 2014). This has been mostly shown in developmental disorders, particularly in ASD, as problem behaviors were identified to be a primary predictor of parental stress (Estes et al, 2013;Zaidman-Zait et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that these parents have increased odds of reporting poor social relations (as neighborhood and friends; Hock & Ahmedani, 2012), more difficulty in adjustment (with coping strategies ;Hastings, 2002;Walsh, Mulder, & Tudor, 2013) and lower level of mental health (high levels of stress and anxiety: Almansour, Alateeq, Alzahrani, Algeffari, & Alhomaidan, 2013;Ruiz-Robledillo & Moya-Albiol, 2013;Seymour, Wood, Giallo, & Jellett, 2013). These findings also revealed that child behavior difficulties may add to parental stress which is well known to be associated to many negative outcomes including anxiety and depression, and may in return influence the use of ineffective coping strategies (Ji et al, 2014;Walsh et al, 2013).…”
mentioning
confidence: 99%
“…For example, in several recent studies, caregivers of children with ASD reported higher levels of negative affective symptoms such as perceived stress , anxiety (Ruiz-Robledillo et al, 2013) and depression (Gallagher & Hannigan, 2014) compared with controls. However, individual difference variables, especially those related to caregivers' personal characteristics such as personal mastery (Cantwell et al, 2014), locus of control (Lloyd et al, 2009) and benefit finding (Kayfitz et al, 2010), have been shown to explain much of the variance in caregivers' subjective feelings of distress.…”
Section: Moderating Role Of Trait Emotional Intelligence?mentioning
confidence: 99%
“…The negative consequences of caring for a relative with a diagnosis of autism spectrum disorder (ASD) have been widely described in previous research (De Andrés-García et al 2012;Ruiz-Robledillo and Moya-Albiol 2013;RuizRobledillo et al 2014). Caring for such a relative is associated with high levels of burden, depression, anxiety, and poorer self-perceived general health (Ruiz-Robledillo and MoyaAlbiol 2013).…”
Section: Introductionmentioning
confidence: 99%